Penerapan Bina Pribadi Islami (BPI) dalam Membentuk Kepribadian dan Karakter Religius Siswa dI SMAIT Hidayah Klaten - Azzacky, Jafar Ihza Yuzka; Inayat, Nurul Latifatul (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This study uses qualitative methodology with a type of descriptive approach. The data obtained were collected through observational data collection techniques, interviews and documentation. Data analysis is carried out by data reduction, data presentation and conclusions. The validity test of the data is carried out by triangulation of sources and techniques, therefore, the author must be careful and thorough in writing the research abstract. This research was motivated by the existence of a special program at SMAIT Hidayah Klaten, namely the Islamic Personal Development program, One of the problems faced by SMAIT Hidayah Klaten, a senior high school based on the Integrated Islamic School (SIT), is the low religious quality of students in terms of creed, sharia, and morals, which results in a lack of personality and religious attitudes of students. Because of this, the school started the Islamic Personal Development program. This activity will definitely go well if there is teacher-student cooperation and good management. This study aims to see how the Bina Pribadi Islami (BPI) program shapes the personality of students at SMAIT Hidayah Klaten. After observation by researchers, the result of this study is an effort to instill the personality and religious character of students, Hidayah Klaten IT High School has an Islamic Personal Development program which is held once a week in rotation, from grade 10 to grade 12. This activity is not only for students but also for teachers, employees and all elements of the school. In it many activities contain the cultivation of Islamic values, especially religious values and worship. The method is also used in the activities of the Islamic Personal Development program, namely lectures, discussions and questions and answers so that students actively participate in these activities